A new submaximal cycle ergometer test for prediction of VO2max. Issue 2 (6th November 2012) - Ekblom‐Bak, E.; Björkman, F.; Hellenius, M.‐L.; Ekblom, B.
<x xml:space="preserve">Abstract</x> Maximal oxygen uptake (VO2max) is an important, independent predictor of cardiovascular health and mortality. Despite this, it is rarely measured in clinical practice. The aim of this study was to create and evaluate a submaximal cycle ergometry test based on change in heart rate (HR) between a lower standard work rate and an individually chosen higher work rate. In a mixed population (n = 143) with regard to sex (55% women), age (21–65 years), and activity status (inactive to highly active), a model included change in HR per unit change in power, sex, and age for the best estimate of VO2max. The association between estimated and observed VO2max for the mixed sample was r = 0.91, standard error of estimate = 0.302 L/min, and mean measured VO2max = 3.23 L/min. The corresponding coefficient of variation was 9.3%, a significantly improved precision compared with one of the most commonly used submaximal exercise tests, the Åstrand test, which in the present study was estimated to be 18.1%. Test–retest reliability analysis over 1 week revealed no mean difference in the estimated VO2max (−0.02 L/min, 95% confidence interval: −0.07–0.03). The new test is low‐risk, easily administered, and valid for a wide capacity range, and is therefore suitable in situations as health evaluations in the general population.